Investigation Of Bilayer Matrix Tablet For Biphasic Delivery Of Loratadine And Pseudoephedrine - Murthy, Bhavanasi Krishna (2015)
The oral route of administration is often preferred due to its convenience, high patient compliance, less stringent production conditions, and lower costs. It has become common to incorporate two or more drugs in a single dosage form, for different indications. In the present study, different designs of matrix tablet systems were examined for their ability in modifying the drug release especially for the delivery of more than one drug at different release rates. The study commenced with the preparation of press coated matrix tablets and a conventional monolithic system with floating features, using paracetamol as a model drug.